Sythesis and characterization of biodegradable grafted copolymers - Moura, I. (2010)
This work aimed to prepare biodegradable copolymers based on ethylene vinyl acetate and polylactic acid using transesterification reactions. The materials were prepared in the melt and then characterized by elemental analysis, infrared spectroscopy, X-ray, scanning electron microscopy, gel permeation chromatography and rheology. Selective extractions for all samples were made, and the results indicate that a maximum of 25% of EVA-g-PLA copolymer was synthesized by this method. Biodegradation tests were carried out using the standard ISO 14851 (1999), which specifies a method for determining the biochemical oxygen demand in a closed respirometer. The results demonstrate that the procedure used allowed the synthesizes of biodegradable copolymers with mechanical properties similar to conventional polymers.